TAKHRIJ HADITH MENGADHANKAN BAYI DALAM KITAB TARBIYAT AL-AWLAD ABDULLAH NASIH ULWAN - Rozali, Muhammad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Adhan for newborns is one of the traditions of a people based on several hadiths of the Prophet Muhammad. After doing some research on the sanad of the hadith, it can be concluded that the hadith had of three lines: Ahmad, Tirmidhi and Abu Dawud. Hadiths are weak because of all `` As{im ibn Ubaidullah, according to scholars of jarh{ wa ta?di>l, is considered weak and munkar al-hadith. But, the hadith of can be practiced (ma?mu>l bih) and could rise to the level of hadith hasan li ghayrih. This means that echoes adhan in both ears newborns areamong the sunnah, even if these problems get in khilafiyah.Keywords: Adhan, Hadith, jarh wa ta?dil